Pension Reforms in Europe : How Far Have We Come and Gone? - Fouejieu, Armand; Kangur, Alvar; Martinez, Samuel; Soto, Mauricio (Washington, D.C. : International Monetary Fund, 2021)
In the past few decades, a myriad of reforms in Europe have had a significant impact on the way and extent to which public pensions provide retirement income. This departmental paper takes stock of where European pension systems stand and assesses their key characteristics. We present a novel measure of the balance between lifetime benefits and contributions-the Proportionality Measure-to examine pension systems' long-term sustainability, fairness, and intergenerational equity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fiscal Policy; Forecasts Of Budgets, Deficits, and Debt; Social Security and Public Pensions